A Real-Time Platform for Collaborative Research on Visible Light Communication - Ribeiro, Carlos Gaspar
This paper reports the implementation and performance results of a real-time Visible Light Communication platform. The platform uses a high-level software abstraction architecture where the algorithms are developed and tested in MATLAB, using a modular architecture. With this modular approach it is very easy to add/remove blocks, making it amenable to collaboration with other groups with interest in this field, offering a real-time test bed to evaluate the performance of different modules, algorithms and optical front-ends, which is currently not available. The physical layer is based on DCO-OFDM and is implemented in a Xilinx Virtex-6 FPGA. We explore the optical front-end out-of-band bandwidth to transmit, showing the usefulness of adopting OFDM-based modulations schemes for VLC. Our system transmits at 2m over an indoor free space channel with 12MHz bandwidth, with more than 23dB gain difference, using QPSK, thus achieving 24Mbit/s with a BER smaller than the usual 3.8x10-3 limit.